STUDY OF THE EFFECT OF STARTER CULTURES ON PRODUCT QUALITY AND THE RIPENING PROCESS IN CHEESE PRODUCTION - S.N.Obloberdiyev,; G.Sh.Korabekova,; F.Sh.G‘ulomova,; M.J.Bekmurodova,; Sh.E.Ulashova,; Z.A.Madusmonova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article studies the effect of starter cultures on cheese quality and the ripening process. The study evaluated the influence of starter cultures on lactic acid formation, pH level, taste, aroma, consistency and storage stability. The results showed that starter culture activity is an important factor in the formation of cheese ripening rate, organoleptic properties and quality indicators.